Skills Development in Sub-Saharan Africa - Johanson, Richard K.; Adams, Arvil V. (Washington, DC: World Bank, 2013)
The review addresses a list of questions that seem especially pertinent for skills development in Sub-Saharan Africa today, namely: What should be the role of training when there is not enough modern sector employment? Given the widespread decay in public training systems, what should be the role of the public sector in training? Are private training providers more cost-effective than public sector training providers? What is the capacity of private training providers to fill the gap left by declining public investment in training? What is the relative importance of training within enterprises and does the state need to intervene to stimulate it? In view of shortages of public financing, how can needed skills development be financed? What role can financing mechanisms play in improving the effectiveness and efficiency of training? Answers to these questions and others developed in each chapter are pursued by looking over the past decade at the structure of employment and the demand for skills; the experience of government and non-government providers of skills training, including enterprises; and the experience with financing of TVET and resource management. The findings yield a clear, strategic role for governments to play in skills development while deepening sector reforms. The actions, if taken, promise to support achievement of the Millennium Development Goals for poverty reduction and Education for All.